DEFICIENCIAS EN LOS MECANISMOS INSTITUCIONALIZADOS DE CONTROL DE VIOLENCIA INTRAFAMILIAR, NO CONTRIBUYEN A LA DISMINUCIÓN SIGNIFICATIVA DE ESTE CONFLICTO SOCIO-JURÍDICO - MENDIETA TACURI, ROBERT ANDRES (2016)
This research aims to present: "Inadequate control institutionalized mechanisms of domestic violence, do not contribute to significant reduction of the socio-legal conflict" that starts from the problematic situation presented. The research is qualitative in nature, with longitudinal descriptive study and type of pre experimental design. The objectives in this research are: To determine the incidence of domestic violence and poor control institutionalized mechanisms of domestic violence do not contribute to the significant decrease of the socio-legal conflict of Lojana Society in 2015, determine the theoretical foundations related to domestic violence and deficiencies in the institutionalized mechanisms of control over the subject, identify the types of domestic violence affecting society and raise Lojana a proposal for legal reform to eradicate domestic violence by supporting the institutionalized relevant agencies. The literature review is part of the variables of domestic violence and institutionalized mechanisms of control of it. According to the requirements of the following research methodology was used, it is descriptive in nature, methods were: deductive, inductive, analytical, descriptive, explanatory and statistical information was obtained through surveys applied. The results were structured in tables and graphs, analysis and interpretation were based on empirical data. The discussion is based on the determination of domestic violence in society Lojana. This thesis is done with a primary objective, the same is to conduct a thorough investigation into the problems caused by domestic violence in society Lojana, also determine which are the causes and effects that carry the victims who have suffered this problem has caused so much damage in the Lojanos homes. That is why according to research conducted, it was possible to conclude that domestic violence is caused by the aggressors in many cases is parents with children, considering that this type of problem directly it affects the integral development of families Lojanas in general.